A Comparative Analysis of Sequential Search Algorithm Implementation within the Sales Information Systems of Wira Thrift Store and Rizky Snack Store - Mugiarso Mugiarso; Marcellino Hutagalung; Miftahur Rizky; Rakhmat Purnomo; Dwipa Handayani; Rasim Rasim (LPPM Universitas Islam 45 Bekasi, 2026)
This study evaluates the implementation of the Sequential Search algorithm to address manual data management challenges within Indonesian MSMEs, specifically regarding stock tracking inefficiencies. The search system was deployed across two distinct entities: Toko Wira Thrift (apparel sector) and Toko Rizky Snack (food sector) using PHP and MySQL. Blackbox testing was conducted through 14 scenarios covering both positive and negative conditions. The results demonstrate that the algorithm successfully enhanced real-time product search speeds for customers and optimized inventory management to prevent stock expiration, achieving a 100% functional success rate. The testing confirms the system's functionality, asserting that Sequential Search is an effective and flexible solution for improving operational efficiency across various MSME sectors.